From Entrepreneurship to Performance: A Capability Chain Perspective in Culinary SMEs - Devi Angrahini Anni Lembana; Christina Juliana; Herlin Hidayat (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2026)
This study investigates the determinants of business performance in the culinary SME sector by developing an integrated capability chain model. The research addresses the challenge of enhancing performance through the interplay of entrepreneurship, human resource quality, networking capability, and management accounting systems, while evaluating sustainability reporting as a potential moderator. Utilizing a quantitative approach, data were gathered from 94 culinary SMEs in the Greater Jakarta area via convenience sampling and analyzed using Partial Least Squares (PLS). Findings reveal a significant sequential pathway where entrepreneurship bolsters HR quality, subsequently driving networking capability and the adoption of management accounting systems to enhance performance. Conversely, sustainability reporting directly impacts performance but not able to moderates the accounting-performance link, suggesting that internal capability development, rather than formal reporting, remains the primary driver of SME success.